Evaluación agronómica del rendimiento del cultivo de la Chía (Salvia hispánica L.) Sometido a la aplicación de tres bioestimulantes foliares a diferentes dosis. - Burbano Pabón, Darío Alfonso (2017)
SUMMARY The present investigation was carried out in the sector of high struts, Canton Bolivar, Carchi province; located in the geographical coordinates: 00 ° 31'16 "north latitude, 77 ° 55'54,4" west longitude at an altitude of 2,980 m.s.n.m. Bioclimatic annual averages are presented as follows: temperature 12 ° C, 750 mm rainfall, relative humidity 70%. ecological classification according to Holdridge dry forests Montano Bajo (bs-MB), according to these results, the type of soil at the site of the experiment is sandy loam. As genetic material variety ted-sol was used chia 80% black and 20% white German origin with an adaptability to different altitudes, and an average temperature genetic material sold INIAP. The treatments were combined days of Factor A: Biostimulants (gibberellins, cytokinins and gibberellins-cytokinin) Factor B: Dose (low, medium and high) and treatment without application (control), the theoretical methods were used: inductive-deductive, analysis synthesis and empirical called experimental, experimental design we used was the design Randomized complete (DBCA) blocks with a factorial arrangement (a x B) + 1 combined, specific treatments for a total of 10 treatments and 3 full repeats of 30 . with the results of the sensitivity test of Tukey was applied to 5% probability. The characteristics of the experimental site was the total area 816,00 m2, the experimental unit of 12.00 m2, the net area of 4.80 m2, the distance between blocks was 1.00 m and 0.60 m between roads. Management assay was developed using the following tasks; soil analysis, soil preparation, demarcation of plots, trenching, planting, irrigation, fertilization, weed control, pest and disease control, application Biostimulants and harvest consisted of cutting and threshing, the variables were, height plant to 30-50 and 80 days after application of the first application of biostimulants, days to flowering, weight per volume, yield and vigor of the stem and the treatments are economically analysis. The results showed more cytokinin determined that the application of Gibberellins Dose Media, significant averages; evaluation of plant height, weight, volume, vigor and yield per experimental unit and reached the highest net income which we can deduce that the combined application of these Biostimulants in Dose Media favored crop development chia production and utility economic.